2018
DOI: 10.1093/heapol/czy059
|View full text |Cite
|
Sign up to set email alerts
|

The role of the traditional leader in implementing maternal, newborn and child health policy in Malawi

Abstract: Traditional leaders play a prominent role at the community level in Malawi, yet limited research has been undertaken on their role in relation to policy implementation. This article seeks to analyse the role of traditional leaders in implementing national maternal, newborn and child health (MNCH) policy and programmes at the community level. We consider whether the role of the chief embodies a top-down (utilitarian) or bottom-up (empowerment) approach to MNCH policy implementation. Primary data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…While traditional leadership in maternal, new-born and child programming seems to strengthen in Malawi [30], we found that they could play a more active role in supporting HSAs in providing contraceptive services. Contraceptive use did not depend upon denomination [14], however, religious leaders seemed 'split' between following the values of their religion, implying contraceptives should not be used, versus accepting people to use contraceptive because of the realities of today.…”
Section: Discussionmentioning
confidence: 70%
“…While traditional leadership in maternal, new-born and child programming seems to strengthen in Malawi [30], we found that they could play a more active role in supporting HSAs in providing contraceptive services. Contraceptive use did not depend upon denomination [14], however, religious leaders seemed 'split' between following the values of their religion, implying contraceptives should not be used, versus accepting people to use contraceptive because of the realities of today.…”
Section: Discussionmentioning
confidence: 70%
“…8 While health policy prior to Malawi's rst democratic elections in 1994 tended to favor private provision of health care, over the last 24 years Malawian policymakers have put forward bold programs to make health care more accessible, including 1994's National Safe Motherhood Program and 2012's Presidential Initiative for Safe Motherhood. [9][10][11][12][13][14][15] In this paper, we estimated the associations between distance to nearest health facility and (i) under-5 mortality, and (ii) maternal health care utilization (place of delivery, receiving a check-up following delivery, number of antenatal visits prior to delivery, or receiving skilled assistance during delivery). We also took a two-way xed effects approach to estimate the causal effect of reductions in distance from the construction of new facilities on those outcomes.…”
mentioning
confidence: 99%
“…Community leaders are considered as an important element for successful community development in Malawi and some parts of Africa [1]. They play a prominent role in establishing and maintaining norms as well as decision-making at the community level [2].…”
Section: Introductionmentioning
confidence: 99%